Rapid evolution of an X-linked microRNA cluster in primates - Zhang, Rui; Peng, Yi; Wang, Wen; Su, Bing (Genome Research, 2007)
MicroRNAs (miRNAs) are a growing class of small RNAs (about 22 nt) that play crucial regulatory roles in the genome by targeting mRNAs for cleavage or translational repression. Most of the identified miRNAs are highly conserved among species, indicating strong functional constraint on miRNA evolution. However, nonconserved miRNAs may contribute to functional novelties during evolution. Recently, an X-linked miRNA cluster was reported with multiple copies in primates but not in rodents or dog. Here we sequenced and compared this miRNA cluster in major primate lineages including human, great ape, lesser ape, Old World monkey, and New World monkey. Our data indicate rapid evolution of this cluster in primates including frequent tandem duplications and nucleotide substitutions. In addition, lineage-specific substitutions were observed in human and chimpanzee, leading to the emergence of potential novel mature miRNAs. The expression analysis in rhesus monkeys revealed a strong correlation between miRNA expression changes and male sexual maturation, suggesting regulatory roles of this miRNA cluster in testis development and spermatogenesis. We propose that, like protein-coding genes, miRNA genes involved in male reproduction are subject to rapid adaptive changes that may contribute to functional novelties during evolution.
10.1101/gr.6146507